Description of some variables in the behaviour of expecting for previously rewards (Psicologia USP, 1991)
The purpose of this experiment was to verify if choice of reward was dependent upon situation knowledge, previous training in self-control or if experimental situation favored self-control learning, here defined as waiting for bigger reward after some time. Having a child in a situation of immediate small reward and a delyed bigger one was the procedure adapted. The timming between both situation was defined as being 15 minutes without child knowledge. A group of 27 children (age 6/7 an 7/10) was selected from a first degree public school file. Those interviewed were considered to have had a previous contact with researcher. Thirteen subjects were not interviewed before experiment took place. Half of the group had the reward visible and half not. These results showed no difference between the two groups regarding immediate delayed reward, previous research acquaintance or visible/not visible reward. The individuals learned with situation and started waiting after being exposed to it. Only three children did not wail for bigger reward even five trials. Most of the individuals started wailing in the first trial or after the second trial. The results arc discussed in term of new experiments needs in which children conversations should be registered in order to better clarify reward, experimental situation and waiting time*.